Relationship between the Teacher Education Students’ Epistemological Beliefs and their Social and Cultural Capital Orientations - Hishan, Sanil S; Ramakrishnan, Suresh; Mansor, Nur Naha binti Abu (International Journal of Psychosocial Rehabilitation, 2020)
Teacher education scholars have proposed that different mechanisms form the actions and behaviors of teachers. This research complements the literature that exists on the connections between the epistemological views and the orientations of Indian teacher education students towards social and cultural property. The study used a concise correlation / survey with a total of 335 respondents. The results indicate that respondents have a strong degree of epistemological confidence in the four dimensions Inner / Fixed Capacity, Effort / Process, Knowledge of Authority / Expert and Certain Information. They also displayed a high degree of social and cultural bias towards capital, with the highest literacy factor. Differences analyses found that mother's education and family earnings are the factors of the epistemological views of the respondents and those who have mothers who are college graduates or high monthly salaries appear to have a strong interest in fast learning. At the other hand, the differential test found that respondents whose parents are highly educated exhibit tremendous social maturity, social stability, cultural ability, and extraversion, social solidity and extraversion. This research found that there is a concordance between Indian teacher education students ' epistemological views and their social and cultural orientations. This indicates that the higher the students ' home literacy habits, the greater the epistemological confidence they continue to achieve in fast learning.